2012
DOI: 10.1111/j.1469-0691.2012.04002.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of material on the development of device-associated infections

Abstract: The use of implanted devices in modern orthopaedic surgery has greatly improved the quality of life for an increasing number of patients, by facilitating the rapid and effective healing of bone after traumatic fractures, and restoring mobility after joint replacement. However, the presence of an implanted device results in an increased susceptibility to infection for the patient, owing to the creation of an immunologically compromised zone adjacent to the implant. Within this zone, the ability of the host to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 53 publications
1
57
1
3
Order By: Relevance
“…Within the scope of the experiment, limited attempts were made to understand how material properties may have contributed to the findings. We found that parylene had a significantly reduced contact angle and appeared smoother in SEM images as compared to bare titanium, potentially providing less opportunity for biofilm formation 20–22 . However, we observed the opposite relationship between contact angle and surface smoothness when parylene was compared to polyurethane.…”
Section: Discussionmentioning
confidence: 62%
“…Within the scope of the experiment, limited attempts were made to understand how material properties may have contributed to the findings. We found that parylene had a significantly reduced contact angle and appeared smoother in SEM images as compared to bare titanium, potentially providing less opportunity for biofilm formation 20–22 . However, we observed the opposite relationship between contact angle and surface smoothness when parylene was compared to polyurethane.…”
Section: Discussionmentioning
confidence: 62%
“…Bacterial adhesion was studied in four different conditions: (1) In normoxia at the presence of PBS, (2) in normoxia at the presence of S53P4 granules using PBS pretreated 2 h with S53P4, (3) in hypoxia at the presence of PBS and 4) in hypoxia at the presence of S53P4 granules using PBS pretreated 2 h with S53P4.…”
Section: Staphylococcal Adhesion Experimentsmentioning
confidence: 99%
“…The presence of an implanted device results in an increased susceptibility to postoperative infection [1,2] because the number of bacteria required to produce an implant infection is reduced [3,4]. This is due to the fact that bacteria adhere easier to an inactive substratum, which is not incorporated to the host defense system.…”
Section: Introductionmentioning
confidence: 99%
“…Upon placement, the device is conditioned by host proteins, such as fibronectin and collagen, which can serve as ligands for bacterial attachment via microbial surface components recognizing adhesive matrix molecules (MSCRAMMS) (4, 9, 11, 15, 106, 107). Therefore, the wound healing responses elicited after medical device implantation can inadvertently provide a rich environment for bacterial colonization; however, they can also set the stage for a very specific immune response that is incapable of mediating bacterial clearance, as described below (108). Staphylococcal biofilm-associated protein (Bap) can facilitate adherence to host epithelial cells through the inhibition of MSCRAMM-mediated attachment (109, 110).…”
Section: Hijacking the Host Responsementioning
confidence: 99%